Low expression levels of microRNA‐124‐5p correlated with poor prognosis in colorectal cancer via targeting of SMC4. (1st August 2014) - Jinushi, Takafumi; Shibayama, Yoshihiko; Kinoshita, Ichiro; Oizumi, Satoshi; Jinushi, Masahisa; Aota, Tadahiro; Takahashi, Toshiyuki; Horita, Shoichi; Dosaka‐Akita, Hirotoshi; Iseki, Ken
Abstract A component of polycomb repressor complex 2, enhancer of zeste homolog 2 (EZH2), plays an important role in tumor malignancy and metastasis, while milk fat globule‐epidermal growth factor‐factor 8 (MFGE8) plays a key role in tumor progression and prognosis. MicroRNAs (miRs) are also critically involved in various physiological and pathological processes. We here evaluated the relationship between overall survival (OS) in colorectal cancer patients and the expression of onco‐miRs and miRs, which may target EZH2 and MFGE8. Plasma and formalin‐fixed paraffin‐embedded (FFPE) samples were obtained from 71 colorectal cancer patients. The expression levels of miRs complementary to EZH2 and MFGE8 mRNA and cancer malignancies were evaluated. The miRs analyzed were as follows: miR‐16, miR‐21, miR‐26a, miR‐34a, miR‐98, miR‐101‐3p, miR‐101‐5p, miR‐124‐5p (also known as miR‐124*), miR‐126‐3p, miR‐126‐5p, miR‐210, miR‐217, and miR‐630. The plasma expression levels of MFGE8 in completely resected patients were significantly lower than those in unresectable patients. Lower miR‐26a expression levels were correlated with a higher probability of OS. Higher miR‐124‐5p expression levels in plasma and FFPE samples were correlated with a higher probability of OS. The transfection of mimic miR‐124‐5p into WiDr and COLO201 cells inhibited the expression of structural maintenance of chromosomes 4 (SMC4) mRNA. Our results indicate that miR‐124‐5p may target the tumorigenesis gene, SMC4, which suggests that expression levels of miR‐124‐5p in plasma and FFPE samples; therefore, the expression of MFGE8, miR‐26a, and miR‐124‐5p in plasma may be used as biomarkers to determine the prognosis of colorectal cancer patients.